Putus Sekolah Akibat Permasalahan Kemiskinan pada Keluarga Miskin di Kampung Petukangan, Jakarta Timur - Ciek Julyati Hisyam; Mayang Puti Seruni; Annisa Intan Maharani; Dela Novi Ardani; Istiharoh Istiharoh; Kailla Putri Aisyah; Lia Karunia Lam Uli Lubis; Pramasheila Arinda Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The phenomenon of school dropout remains a serious issue in Indonesia’s education system, particularly in urban poor areas such as Kampung Petukangan, East Jakarta. This study aims to understand how poverty, both in its absolute and relative forms, contributes to children's decisions to leave school, as well as how the education system plays a role in reproducing social inequality. Using a qualitative approach with in-depth interviews and limited participant observation, the research was conducted with five informants, consisting of school dropouts and their parents. The analysis draws on Pierre Bourdieu’s theoretical concepts, including habitus, capital, field, symbolic violence, and social reproduction. The findings indicate that dropping out of school is not merely an individual decision, but the result of a complex interaction between economic structures, the habitus of poor families, a lack of social and cultural capital, and symbolic mechanisms within the education system that subtly exclude disadvantaged children. Instead of serving as a tool for social mobility, school functions as an arena that reproduces class inequality across generations.